Pemberdayaan Masyarakat Desa Wisata Berbasis Kearifan Lokal di Desa Batubulan - Junaidi, Junaidi (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2025)
In the current technological era, the growth of the tourism industry in rural areas is increasingly linked to other industries such as agriculture, manufacturing, and healthy and natural lifestyles. The purpose of this research is to study the possibilities and difficulties in building tourism value in rural areas by using an integrated business approach while maintaining the local culture of the village community. This happened in Batubulan Village in Sukawati District, Gianyar Regency, Bali Province. To get information, people look at and analyse documents from various sources, such as books, papers, and articles on the internet. Members of the community service team of Sjakhyakirti University and Association of Connecting Lecturers-Collaboration of Lecturers Across Countries (CeL-KODELN) Indonesia engaged in Focus Group Discussion (FGD) to assess the potential of the village. The results of the service before the programme showed that participants scored 1.89 in their understanding and knowledge of how to develop a tourism village, while the analysis after the service activity showed that participants scored 11.22 in their knowledge of discussion and question and answer techniques. This shows that the strategies used in this initiative are very effective. This service activity discovered the tourism potential of Batubulan Village, including nature tourism, agro-tourism, historical heritage, culinary, and healthy and natural green tourism. The purpose of this activity is to increase the added value of the tourism village through local wisdom and increase the income of the village community.